Further study on kinetic modeling of sunflower oil methanolysis catalyzed by calcium-based catalysts - Miladinović Marija R.; Tasić Marija B.; Stamenković Olivera S.; Veljković Vlada B.; Skala Dejan U. (Chemical Industry and Chemical Engineering Quarterly, 2016)
The kinetic model, which was originally developed for sunflower oil methanolysis catalyzed by CaO.ZnO, was examined for several other calcium-based catalysts like neat CaO, quicklime and Ca(OH)2. This model including triacylglycerols mass transfer- and chemically-controlled regimes demonstrated a good agreement with the experimental data in terms of a high coefficient of determination (0.971±0.022) and acceptable mean relative percentage deviation (±15.9%). Hence, this model is recommended for modeling the kinetics of sunflower oil methanolysis over calcium-based catalysts under widely ranging reaction conditions. [Projekat Ministarstva nauke Republike Srbije, br. III 45001]